The Reasoning of Integrative Islamic Religious Education from Al-Qabisiy's Perspective - Muvid, Muhamad Basyrul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
Islamic religious education must always improve and be developed in all aspects to create an integrative education system or model, because digital progress, intense competition, and complex needs require education to be adaptable and dynamic to produce graduates who are competitive in addition to being ethical and humane. Therefore, this study aims to examine and analyze Al Qabisiy's thoughts as one of the reformers of Islamic education. This research uses a type of qualitative research with a literature study approach, namely the source of the study is taken from data in the form of books, journals, the internet, and other supporting documentation, then the analysis technique uses interpretation (interpretation) which is strengthened by relevant reference sources. The results showed that Al Qabisiy wanted to realize Islamic education that was friendly, complex, balanced, and dignified in accordance with the Qur'an and the morals of the Prophet Muhammad, a complete education with attention to affective, cognitive, and psychomotor aspects, always upholding the honor of students, especially students women, and presents complex learning, namely between the sciences of recitation and ikhtiyari. Thus, Islamic education can run well and will be able to produce graduates who are competent, religious, and ethical who bring benefits to people's lives universally.